Analysis of the Influence of Price Discount and Hedonic Shopping on Impulse Buying at Arni Store - Sintiani S; Marianti Pare Lobo’; Rosdiana R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to determine the effect of price discounts and hedonic shopping on impulse buying at Arni Store. The data used are primary. The research method used is a comparative research method with a quantitative approach and multiple linear regression techniques to measure the relationship between variables. The analysis results indicate that price discounts and hedonic shopping have a positive and significant effect on impulse buying at Arni Store.